A diez años de la publicación del Motu Proprio Omnium in mentem = On the ten-year anniversary of the Motu Proprio Omnium in mentem - Lloréns, Inés (Ius canonicum, 2020)
Ten years have passed since the publication of the Motu Proprio Omnium in mentem, a norm that removed the clause concerning the formal act of abandonment from the Code of Canon Law and, along with it, some technical mechanisms linked to that provision. The purpose of this paper is to explore the legal-pastoral repercussions of this legal measure. To this end, the causes that prompted the promulgation of the Motu Proprio are described, as is the process by which it was drafted, focusing in particular on the doctrinal and disciplinary implications the law may entail, and offering an assessment of its appositeness.